INNOVATIVE DEVELOPMENT OF SERVICES EXPORT OF UKRAINIAN IN CONDITIONS OF PEACE AND WAR - Kliuvak , O. V. (The actual problems of regional economy development, 2022)
The system of international trade is one of the key drivers of the development of the world economy in the context of globalization that contains exports-imports of goods and services. Despite the large number of papers dedicated to the functioning of the export system it should be noted that the sphere of export of services has been insufficiently studied and highlighted. The importance of the research of innovative development of exports of services of Ukraine is deepened by the fact that the export of goods has declined significantly after a full-scale military russian invasion into Ukraine and its complete recovery will take a long time. The essence of the export of services through the prism of its four models (cross-border supply of services, consumption abroad, commercial presence, the presence of natural persons) is considered in the article. The structure of foreign trade in services of Ukraine in 2021 is analyzed. It is established that the sphere of telecommunications, computer and information services is a promising area of export specialization in conditions of modern russian-ukrainian war. The approach to the formation of the system of innovative development of enterprises in the service sector in the context of Ukraine's export strategy, globalization processes and martial law is developed. The main tools of services export support of Ukraine in conditions of the russian-ukrainian war are systematized and the particular attention is focused on expediency of activating and implementing the European concept of smart specialization of regions. The direction of improving the export system of Ukraine in wartime and postwar times is suggested. It takes into account: the implementation of the European concept of smart specialization of regions focusing on the service sector, in particular the creative, tourist, recreational and information industries of those territories of Ukraine that have suffered less due to full-scale invasion of Ukraine by the armed forces of the russian federation; model of development of export-oriented enterprises in the service sector based on FinTech innovations, use of Industry 4.0 technologies and eco-innovation.